Clinical Decision Support for High-Risk Stage II Colon Cancer: A Real-World Study of Treatment Concordance and Survival. Issue 10 (October 2020) - Chen, Peng-ju; Li, Tian-le; Sun, Ting-ting; Willis, Van C.; Roebuck, M. Christopher; Bravata, Dena M.; Liu, Xin-zhi; Arriaga, Yull E.; Dankwa-Mullan, Irene; Wu, Ai-wen
Abstract : BACKGROUND: Prognostic and pathologic risk factors typically guide clinicians and patients in their choice of surveillance or adjuvant chemotherapy when managing high-risk stage II colon cancer. However, variations in treatment and outcomes in patients with stage II colon cancer remain. OBJECTIVE: This study aimed to assess the survival benefits of treatments concordant with suggested therapeutic options from Watson for Oncology, a clinical decision support system. DESIGN: This is a retrospective observational study of concordance between actual treatment and Watson for Oncology therapeutic options. SETTING: This study was conducted at a top-tier cancer center in China. PATIENTS: Postoperative treatment data were retrieved from the electronic health records of 306 patients with high-risk stage II colon adenocarcinoma. MAIN OUTCOME MEASURES: The primary outcomes measured were the treatment patterns plus 3- and 5-year overall and disease-free survival for concordant and nonconcordant cases. RESULTS: Overall concordance was 90%. Most nonconcordant care resulted from adjuvant chemotherapy use (rather than surveillance) in patients with high-level microsatellite instability and ≥70 years old. No difference in overall survival ( p = 0.56) or disease-free survival ( p = 0.19) was observed between concordance groups. Patients receiving adjuvant chemotherapy had significantly higher 5-year overall survival than those undergoing surveillance (94% vs 84%, p = 0.01). LIMITATIONS: This study was limited by the use of retrospective cases drawn from patients presenting for surgery, the lack of complete follow-up data for 58% of patients who could not be included in the analysis, and a survival analysis that assumes no unmeasured correlation between survival and censoring. CONCLUSIONS: Watson for Oncology produced therapeutic options highly concordant with human decisions at a top-tier cancer center in China. Treatment patterns suggest that Watson for Oncology may be able to guide clinicians to minimize overtreatment of patients with high-risk stage II colon cancer with chemotherapy. Survival analyses suggest the need for further investigation to specifically assess the association between surveillance, single-agent and multiagent chemotherapy, and survival outcomes in this population. See Video Abstract at http://links.lww.com/DCR/B291 . APOYO A LA DECISIÓN CLÍNICA DEL CÁNCER DE COLON EN ESTADIO II DE ALTO RIESGO: UN ESTUDIO DEL MUNDO REAL SOBRE LA CONCORDANCIA DEL TRATAMIENTO Y LA SUPERVIVENCIA: ANTECEDENTES: Los factores de riesgo pronósticos y patológicos generalmente guían a los médicos y pacientes en su elección de vigilancia o quimioterapia adyuvante cuando se trata el cáncer de colon en estadio II de alto riesgo. Sin embargo, las variaciones en el tratamiento y los resultados en pacientes con cáncer de colon en estadio II permanecen. OBJETIVO: Evaluar los beneficios de supervivencia de los tratamientos concordantes con las opciones terapéuticas sugeridas por "Watson for Oncology" (Watson para la oncología), un sistema de apoyo a la decisión clínica. DISEÑO: Estudio observacional retrospectivo de concordancia entre el tratamiento real y las opciones terapéuticas de Watson para oncología. AJUSTE: Un centro oncológico de primer nivel en China. PACIENTES: Datos de tratamiento postoperatorio de registros de salud electrónicos de 306 pacientes con adenocarcinoma de colon en estadio II de alto riesgo. PRINCIPALES MEDIDAS DE RESULTADO: Patrones de tratamiento más supervivencia global y libre de enfermedad a 3 y 5 años para casos concordantes y no concordantes. RESULTADOS: La concordancia general fue del 90%. La mayoría de la atención no concordante resultó del uso de quimioterapia adyuvante (en lugar de vigilancia) en pacientes de alto nivel con inestabilidad de microsatélites y pacientes ≥70 años. No se observaron diferencias en la supervivencia global ( p = 0, 56) o la supervivencia libre de enfermedad ( p = 0, 19) entre los grupos de concordancia. Los pacientes que recibieron quimioterapia adyuvante tuvieron una supervivencia global a los 5 años significativamente más alta que los que fueron sometidos a vigilancia (94% frente a 84%, p = 0, 01). LIMITACIONES: Uso de casos retrospectivos extraídos de pacientes que se presentan para cirugía, falta de datos de seguimiento completos para el 58% de los pacientes que no pudieron ser incluidos en el análisis, y análisis de supervivencia que asume que no exite una correlación no medida entre supervivencia y censura. CONCLUSIONES: Watson para Oncología produjo opciones terapéuticas altamente concordantes con las decisiones humanas en un centro oncológico de primer nivel en China. Los patrones de tratamiento sugieren que Watson para Oncología puede guiar a los médicos para minimizar el sobretratamiento de pacientes con cáncer de colon en estadio II de alto riesgo con quimioterapia. Los análisis de supervivencia sugieren la necesidad de realizar mas investigaciónes para evaluar específicamente la asociación entre la vigilancia, la quimioterapia con uno solo o múltiples agentes y los resultados de supervivencia en esta población. Consulte Video Resumen en http://links.lww.com/DCR/B291 . (Traducción—Dr. Gonzalo Hagerman ) Abstract : Supplemental Digital Content is available in the text.